American tall tales - Osborne, Mary Pope.; McCurdy, Michael (New York : Knopf, 1991)
A collection of tall tales about such American folk heroes as Sally Ann Thunder Ann Whirlwind, Pecos Bill, John Henry, and Paul Bunyan.
Includes bibliographical references (p. 111-115).
Keywords: Tales -- United States; Tall tales -- United States; Tall tales; Folklore -- United States